Pengaruh Kompetensi Pedagogik Dan Pengalaman Mengajar Guru Terhadap Kemampuan Mengajar Digital - Revi Setiawan (Yayasan Al-Afif, 2026)
In the context of digital learning, pedagogical competence serves as a crucial foundation for determining the appropriate approach to technology use. However, many teachers still experience difficulties in integrating pedagogical aspects with the optimal use of digital technology, indicating that such competence still needs to be systematically developed within the framework of educational digital transformation. This study aims to: (1) describe teachers’ pedagogical competence, (2) describe their teaching experience, (3) describe their digital teaching ability, and (4) analyze whether pedagogical competence and teaching experience have a significant influence on digital teaching ability. This research employed a descriptive quantitative approach. The research instrument used was a questionnaire. The sample consisted of 81 respondents, determined from the population using the Slovin formula. Data were analyzed using descriptive and inferential statistical techniques. Descriptive analysis included calculating frequency tables, mean, mode, median, variance, standard deviation, histogram, and polygon, while inferential analysis employed regression and correlation analysis. The results showed that: first, pedagogical competence was predominantly in the “good” category (76.2%); second, teaching experience was also in the “good” category (76.8%); and third, digital teaching ability was mainly in the “good” category (75.31%). The normality test results for all variables pedagogical competence, teaching experience, and digital teaching ability indicated that the data were normally distributed, thus accepting the null hypothesis (H₀). In conclusion, pedagogical competence and teaching experience simultaneously have a significant influence on teachers’ digital teaching ability. This finding demonstrates that both variables complement each other in shaping teachers’ capacity to face educational challenges in the digital era. The researcher suggests providing supporting facilities for digital learning such as internet access, digital devices, and e-learning platforms; fostering a collaborative culture among teachers to share digital-based teaching experiences; expanding teacher training programs focused on digital transformation; and continuously strengthening human resources in every school through sustainable training programs.